2017
DOI: 10.1097/hmr.0000000000000093
|View full text |Cite
|
Sign up to set email alerts
|

Work-related factors influencing home care nurse intent to remain employed

Abstract: Home care organizations can promote home care nurse intent to remain employed by (a) ensuring nurses have adequate training and resources to provide quality client care, (b) improving employment conditions to increase income stability and satisfaction with pay and benefits,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
41
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 23 publications
5
41
1
Order By: Relevance
“…This finding is in line with research by Tourangeau et al. (), who show that having variety in patient situations is positively related with home‐care nurses’ intent to remain employed in home care.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This finding is in line with research by Tourangeau et al. (), who show that having variety in patient situations is positively related with home‐care nurses’ intent to remain employed in home care.…”
Section: Discussionsupporting
confidence: 92%
“…Previous research also points to some other aspects that attract nurses to work in home care, such as good employment conditions, use of their skills and abilities, having sufficient time to provide high quality nursing care, supportive supervisors and flexibility (Amstrong‐Stassen & Cameron, ; Anthony & Milone‐Nuzzo, ; Tourangeau, Patterson, Saari, Thomson, & Cranley, ). However, previous studies on the attractive aspects of working in home care were mainly quantitative in nature, and in‐depth knowledge of what attracts home‐care nurses is lacking, for instance with regard to the kind of autonomy that home‐care nurses find attractive.…”
Section: Introductionmentioning
confidence: 99%
“…A Belgian study found that task autonomy, social support and opportunities for learning could buffer workplace stresses (Vander Elst et al, ). A recently published Canadian study (Tourangeau, Patterson, Saari, Thomson, & Cranley, ) confirmed our findings that HCN retention was related to a number of modifiable factors including: income stability, meaningfulness of work, continuity of care, positive relationships with supervisors, work‐life balance, and satisfaction with salary and benefits. One factor related to retention in this study that was not revealed in our review included nurses’ perceptions of the quality of care provided by their organisation (Tourangeau et al, ).…”
Section: Discussionsupporting
confidence: 86%
“…This study incorporated a cross-sectional survey design and is part of a larger study examining factors influencing HC nurses' retention (Tourangeau et al 2017). In study phase 1 focus group, HC nurses identified factors that influenced their decision to remain in or leave HC (Tourangeau et al 2014).…”
Section: Methodsmentioning
confidence: 99%
“…One element of focus group discussions focused on occupational hazards faced in HC work. In study phase 2, HC nurses were invited to complete a survey developed from focus group findings and previous literature to understand their intention to remain employed and those factors influencing these intentions (Tourangeau et al 2017). This paper reports on the phase 2 survey responses of the 14 occupational hazards with specific focus on their prevalence across different geographical settings.…”
Section: Methodsmentioning
confidence: 99%